pengaruh budaya organisasi terhadap mahasiswa di kota palopo: pengaruh budaya organisasi terhadap mahasiswa di kota palopo - Vioni Aulia; , Mutia Nurfadilah Aris; Haedar Haedar (Universitas Slamet Riyadi, 2024)
This research aims to determine the influence of organizational cultural values ​​on students in Palopo City. This research was conducted using quantitative methods. The population used was all students in the city of Palopo and 37 of them were used as samples. The sample in this study used simple random sampling. From this research it was found that there is an influence between organizational culture variables (X) on students (Y). This is proven through the t test. Where the results obtained with t count are greater than t table or t count 4.558 > 1.590 t table then there is an influence of variable X on Y. Organizational culture has a significant effect on students in Palopo City. It is hoped that the results of this research can provide information for consideration, support and contribution of thought to readers regarding the influence of organizational culture on students. The limitations of this research are: lack of samples studied, only using validity tests and t tests, using organizational culture (X) and student (Y) influence variables, and lack of knowledge of the authors